Croatia : Where Are We Since the COVID-19 Outbreak? - World Bank (World Bank, Washington, DC, 2021)
This report focuses on the impact of Coronavirus (COVID-19) outbreak in Croatia as of March 2021. The data was collected through the rapid response household surveys representing Croatian households.